Efficacy of Internet-Based Cognitive Behavioral Therapy for Subthreshold Depression Among Older Adults in Institutional Long-Term Care Settings: Pragmatic Randomized Controlled Trial - Fanqian Kong; Libo Yu; Yanbin Hou; Lijie Zhu; Jing Zhou; Lingjie Huang; Yueer Lv; Li Wang; Li Zhang; Yiling Yang; Yuchen Ying (JMIR Publications, 2024)
BackgroundSubthreshold depression (sD) is prevalent in older populations in long-term care (LTC) settings, but psychological therapy in LTC settings in China is not readily available. Thus, internet-based cognitive behavioral therapy (ICBT) may be suitable for this population, but research on the efficacy of ICBT for older adults with sD, especially those living in LTC settings, is limited. ObjectiveThis study aimed to evaluate the efficacy and acceptability of ICBT treatment for sD among LTC residents in China. We also examined whether ICBT is as effective as group-based cognitive behavioral therapy (CBT) for treating sD in this population. MethodsWe conducted a pragmatic randomized controlled trial, which included 18 LTC institutions. A total of 354 participants were randomized to ICBT, group-based CBT, or a waiting list and were followed up for 12 months. The primary outcome was self-reported depressive symptoms on the Center for Epidemiological Studies Depression Scale (CES-D). Secondary outcomes were the scores of the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder 7-Item (GAD-7), and Geriatric Depression Scale (GDS). A mixed-effects model was used to assess the efficacy of ICBT. ResultsThe ICBT group showed a significant improvement in self-reported depressive symptoms, which was maintained at the 12-month follow-up (all P<.001). The ICBT group exhibited a significantly larger reduction in the scores of the CES-D (Cohen d=0.07, 95% CI 0.04-0.09; P=.01), PHQ-9 (d=0.30, 95% CI 0.28-0.33; P<.001), GDS (d=0.10, 95% CI 0.08-0.13; P<.001), and GAD-7 (d=0.19, 95% CI 0.17-0.22; P<.001) compared with a waiting list at postintervention. ICBT had significantly stronger effects than CBT on the PHQ-9 and GAD-7 at postintervention (d=0.15, 95% CI 0.13-0.17; P<.001 and d=0.21, 95% CI 0.19-0.23; P<.001, respectively), 6-month follow-up (d=0.18, 95% CI 0.16-0.21; P<.001 and d=0.18, 95% CI 0.15-0.21; P<.001, respectively), and 12-month follow-up (d=0.15, 95% CI 0.11-0.19; P<.001 and d=0.18, 95% CI 0.14-0.21; P<.001, respectively). ConclusionsICBT is a relatively effective and acceptable intervention for reducing depressive symptoms among Chinese LTC residents with sD. These findings indicate the usefulness of ICBT application for sD in LTC settings. Trial RegistrationChinese Clinical Trial Registry ChiCTR2000030697; https://www.chictr.org.cn/showproj.aspx?proj=50781